Rebalancing : Evidence from Current Account Adjustment in Europe - Atoyan, Ruben (IMF Working Papers; Working Paper ;, 2013)
After the 2003-2007 economic boom, European countries with large pre-crisis current account imbalances are undergoing adjustments. Countries are adjusting at different paces and ways reflecting the source and magnitude of imbalances, availability of financing, competitiveness of the tradable sector and external environment. While emerging European countries with large pre-crisis imbalances and a fixed exchange rate regime have seen sharp current account adjustments and a rebound in growth, adjustment in the euro zone periphery countries, which are also carrying a legacy of pre-crisis CA imbalances, has been gradual with difficulties bringing back growth. This paper is an empirical investigation of current account adjustment in Europe with a focus on these two groups, looking at contributions from cyclical and other factors, and seeking to draw policy conclusions.